Effect of Textual Errors on The Evaluation of a Foreign Online Store - Lesma, Vanessa Bracamonte; Okada, Hitoshi (International Journal of Informatics and Information Systems, 2020)
We conducted an experimental study among Japanese consumers to investigate the impact of textual errors on the perception and evaluation of an online store in a cross-border context. In particular, we proposed that the presence of textual errors would result in lower perceived ease of use, ease of communication and trust in a foreign online store. The experiment considered two types of errors, related to the use of language and to the completeness of translation. Four experimental conditions with different levels of textual errors were evaluated. We conducted a survey in Japan, obtaining a total of 1919 responses which were analyzed using structural equation modeling. The results showed that the presence of textual errors had a negative effect on all factors in the proposed model, compared to the absence of such errors. We discuss these results and their implications for foreign online vendors.